Оптическое пропускание керамики, изготовленной из коммерческого нанопорошка MgAl2O4 c добавкой LiF - Лян Линьсинь; Хуан Фули; Деулина Д. Е. Дарья Евгеньевна; Шевченко И. Н. Иван Николаевич; Пайгин В. Д. Владимир Денисович (2024, 2024)
Текстовый файл